Genetic Analysis of a Horizontal Resistance Locus BLMR2 in Brassica napus - Zhang, Qiang; Dandena, Hanna; McCausland, Madison; Liu, Huizhi; Liu, Zheng; Xu, Wen; Li, Genyi (Frontiers in Plant Science, 2021)
Leptosphaeria maculans causes blackleg disease in Brassica napus. The blackleg disease is mainly controlled by resistance genes in B. napus. Previous studies have shown that the blackleg resistant BLMR2 locus that conferred horizontal resistance under field conditions, is located on chromosome A10 of B. napus. The purpose of this study is to fine map this locus and hence identify a candidate gene underlying horizontal resistance. The spectrum of resistance to L. maculans isolates of the resistance locus BLMR2 was analyzed using near isogenic lines, resistant, and susceptible cultivars. The results showed that this locus was horizontally resistant to all isolates tested. Sequence characterized amplified regions (SCAR), simple sequence repeats (SSR), and single nucleotide polymorphism (SNP) markers were developed in the chromosome region of BLMR2 and a fine genetic map was constructed. Two molecular markers narrowed BLMR2 in a 53.37 kb region where six genes were annotated. Among the six annotated genes, BnaA10g11280D/BnaA10g11290D encoding a cytochrome P450 protein were predicted as the candidate of BLMR2. Based on the profiling of pathogen induced transcriptome, three expressed genes in the six annotated genes were identified while only cytochrome P450 showed upregulation. The candidate corresponds to the gene involved in the indole glucosinolate biosynthesis pathway and plant basal defense in Arabidopsis thaliana. The molecular markers identified in this study will allow the quick incorporation of the BLMR2 allele in rapeseed cultivars to enhance blackleg resistance.